MENGEMBANGKAN ENTREPRENEURSHIP SEJAK USIA DINI MELALUI KEGIATAN MARKET DAY - Iis Susanti; Washilla, Fadhilla; Yetri; Badarudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the era of global disruption and uncertain economic dynamics, fostering an entrepreneurial spirit from an early age is no longer just an option, but a strategic urgency. Early childhood education plays a crucial role as the foundation for character and mindset formation. "Market Day" activities represent one of the efforts to build and nurture this entrepreneurial spirit in children from the very beginning. Through Market Day, children engage in a direct learning process, implementing the concept of "Learning by Doing." Consequently, they can experience firsthand the entire process required in entrepreneurial activities. Cultivating an entrepreneurial spirit from an early age is vital in preparing a future generation that is independent, creative, and adaptive.